Analysis Of The Montessori Method In Beginning Reading Skills Of Indonesian Subjects In Of Students Sd Negeri 1 Jatiwaringin - Ika Ayudya Purnama Sary; Tatat Hartati; Rony Wirachman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The Montessori method is a method in the realm of child development education and is formulated based on Montessori theory. This method emphasizes the activities that are raised by the child by emphasizing the process of adapting the child's learning environment according to the stage of development. Mastery of reading skills in schools is one of the language competencies that must be taught. This study aims to describe how the Montessori method improves beginning reading skills in SD Negeri 1 Jatiwaringin students. This research method uses descriptive qualitative with data collection techniques in the form of oral, written test results, interviews and direct observation. The Montessori method seeks to help students develop cognitive, psychomotor, and affective abilities in students, by enabling children to learn according to their level of development.